Nuclear quantum effects on the structure and energetics of (H2O)6H+. - Mella, M; Kuo, J; Clary, D; Klein, M (2005)
The energetics and structure of the protonated water hexamer (H2O)6H+ have been examined employing both model potentials and high-level ab initio methods. To select candidate structures for this cluster, Parallel-Tempering and the OSS2 potential were used as devices to complement the set of stationary points previously optimized by Hodges and Wales, Chem. Phys. Lett., 2000, 324, 279. Structures of these local minima were successively re-optimized using OSS3, B3LYP/aug-cc-pVDZ, and MP2/aug-cc-pVDZ, the latter providing a reference to benchmark the performance of the empirical models and B3LYP method. We found that both OSS2 and OSS3 require a re-parameterization to adequately describe the energetics of some isomers. Zero point energy was found to be important in defining the relative stability of the optimized isomers. The effect of the anharmonicity on the vibrational ground state of (H2O)6H+ was also examined by means of diffusion Monte Carlo (DMC) and the OSS3 potential, and we found that it accounts for a decrease in total energy of roughly 0-4.4 mE(h). This is a significant effect on the energetics considering that many isomers are nearly degenerate. Including the anharmonic corrections computed with DMC, the branched species were found to be the most stable isomers. The height of the barriers separating a cage or cyclic isomer from a branched one was found to vary from 1.5 to 5.8 mE(h).